Develoment of ozone-dynamic technology for processing of used tyres - Golota, V.I.; Taran, G.V.; Zamuriev, A.A. (Вопросы атомной науки и техники, 2015)
The results of research on the influence of different factors on disintegration of rubber goods by the ozone-dynamic method are presented. The dependence of disintegration rate on the time of treatment, temperature and humidity of gas in the chamber, ozone concentration and the activating chemical reagents were studied. This allows increasing efficiency of rubber goods processing by 30%. The dependence of the starting time for disintegration stages on ozone concentration in the chamber was determined. This allows optimizing the process of disintegration for rubber goods and gives the mechanism to control the process. Приведено результати досліджень впливу різних чинників на дезинтеграцію гумотехнічних виробів озоно-динамічним методом. Визначена залежність ступеня дезинтеграції від часу дії, температури та вологості газу в камері, концентрації озону і наявності хімічних реагентів у складі робочого газу. Це дозволило підвищити ефективність процесу переробки гумотехнічних виробів майже на 30%. Визначена залежність часу початку настання етапів дезинтеграції гумотехнічних виробів від концентрації озону в камері. Це дозволить оптимізувати процес дезинтеграції гуми і дасть можливість управляти процесом. Приведены результаты исследований влияния различных факторов на дезинтеграцию резинотехнических изделий озоно-динамическим методом. Определены зависимости степени дезинтеграции от времени воздействия, температуры и влажности газа в камере, концентрации озона и наличия химических реагентов в составе рабочего газа. Это позволило повысить эффективность процесса переработки резинотехнических из-делий почти на 30%. Определена зависимость времени начала наступления этапов дезинтеграции резинотехнических изделий от концентрации озона в камере. Это позволит оптимизировать процесс дезинтеграции резины и даст возможность управлять процессом.